A Jurisprudential Analysis of the Maqasid of Preserving Life and Its Impact on Formulating Health Policies in Islamic Countries - Ali G. Al Zuraib, Mohammd; Al-Qahtani, Waleed Khalid (Journal of Neonatal Surgery, 2025)
The objective of preserving life is one of the most fundamental goals (maqasid) in Islamic law. Societal interests cannot be fulfilled nor can communal structures be stabilized without protecting human life. This maqasid has deeply influenced various areas of Islamic jurisprudence, especially those related to medicine, treatment, and health security. This study seeks to analyze the juristic foundations of this objective and its direct influence on public health policymaking in Islamic countries. It investigates how different Islamic schools of thought provide a sustainable legal basis for promoting the health of individuals and societies. The study employs an analytical and comparative methodology, integrating higher objectives of Shariah and encompassing economic, social, and medical dimensions